Dominasi Asing di Pasar Modal dalam Perekonomian Indonesia - Esta Lestari (Jurnal Ekonomi dan Pembangunan, 2025)
Increasing portion of foreign ownership in Indonesia Capital Market bring about debates on either advantage or disadvantage on the economy. On one hand, foreign ownership would induce higher dependency of the economy to the external global. Shocks, subsequently increase domestic risks. On the other hand, foreign ownership resultst on more investment and liquidities for the country that would be giving long term benefits through capital acceleration. This study examines impact of foreign pwnership and its risk to the capital market, as indicated by dynamics of capital market's volatility of Indonesia (BEI). Employing EGARCH(1,1) model, the study finds that Indonesian capitla market is intensively integrated to the world market, especially regional market of Asia compared to the US. Morever, by using OLS model to analyse factors affecting volatility of the market, the results show that along with increasing foreign trading frequencies would lead to positive impact on volatility. In other words, increasing foreign ownership would give less volatility in capital markets and therefore shows characteristics of stabilizing. Other variables are also indicated as factors affecting voaltility of markets, namely interest rates, exchange rate, and previous return.